Motivation among physicians in Greek public health-care sector - Tsounis, Andreas; Bamidis, Panagiotis D.; Sarafis, Pavlos (My University, 2014)
Aims: The aim of this study is to examine the issue of motivation of physicians employed at Greek public hospitals. Methodology: Through the review of relevant literature, an attempt to examine the trends in this issue in Greek public health care sector has been made. Various electronic databases were searched by the authors and through systematic selection 41 scientific articles, studies and electronic sources were identified, that this literature review is based on. The selection was based in two different criteria : for the theoretical background of the issue of motivation, articles and books that considered to be fundamental for the formulation of the subsequent theories were selected, while for the relevant to the main research question literature (motivation in Greek physicians) the most recent data were selected. Results: Motivation of doctors is a highly complex issue that presents an intense differentiation compared with other aspects of staff handling. According to the literature, financial incentives cannot by themselves motivate physicians. On the contrary, the development and utilization of incentives that are associated with achievement of goals, possibility of professional development and recognition in the workplace, appears more effective. Conclusion: Proper diagnosis of the needs of the doctors in the hospital and the selection of appropriate techniques, as these arise through various theories of motivation, can help in the efficiency and efficacy of health care services. Especially in a time of prolonged economic downturn, while the health needs of the population are increased and budgetary constraints compound the difficulties of their effective coverage, searching for administration models that will be able to take full advantage of material and human resources are inevitably in the spotlight of our interest.
Keywords: Motivation; Physicians; Human needs; Public hospital; Incentives